2014
DOI: 10.3748/wjg.v20.i25.8201
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase3a expression is an independent poor prognostic indicator in gastric cancer

Abstract: The results suggest that expression of DNMT3a is an independent poor prognostic indicator in gastric cancer. DNMT3a might play an important role in gastric carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…3C and D revealed the expression profile of the DNMTs similar to IHC results. Substantial research has shown that DNA methylation appears in the cancerous and para-cancerous tissues (30), these data are in agreement with our present study.…”
Section: Expression Of Dnmts Is Significantly Upregulated In Para-carsupporting
confidence: 94%
“…3C and D revealed the expression profile of the DNMTs similar to IHC results. Substantial research has shown that DNA methylation appears in the cancerous and para-cancerous tissues (30), these data are in agreement with our present study.…”
Section: Expression Of Dnmts Is Significantly Upregulated In Para-carsupporting
confidence: 94%
“…As important DNMTs for de novo methylation [16,17], DNMT3A and 3B have been found to be overexpressed in various tumors including GBM [18][19][20][21], and responsible for the epigenetic silencing of multiple tumor suppressor genes [22]. Although it has been accepted that miR-29s could restore the expression of tumor suppressors by silencing DNMT3A/3B [4,18,[23][24][25][26], the real mechanisms are still controversial.…”
Section: Discussionmentioning
confidence: 97%
“…Hypermethylation is responsible for the silencing of TSGs involved in tumorigenesis (19,20). DNMT3A, like other DNMT family members, is involved in tumorigenesis, differentiation and metastasis (21,22), but the correlation between DNMT3A and NSCLCs remains largely unknown. In the last ten years, miRNAs have been noted to play a significant role in the initiation and progression of NSCLCs (23,24).…”
Section: Discussionmentioning
confidence: 99%